1999
DOI: 10.1016/s1074-7613(00)80147-8
|View full text |Cite
|
Sign up to set email alerts
|

Attrition of T Cell Memory

Abstract: Using a variety of techniques, including limiting dilution assays (LDA), intracellular IFNgamma assays, and Db-IgG1 MHC dimer staining to measure viral peptide-specific T cell number and function, we show here that heterologous virus infections quantitatively delete and qualitatively alter the memory pool of T cells specific to a previously encountered virus. We also show that a prior history of a virus infection can alter the hierarchy of the immunodominant peptide response to a second virus and that virus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(63 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…Mice infected with EV 71 failed to produce type I IFN in response to either poly(I:C) injection or CVB3 infection, both of which are strong inducers of type I IFN [14]. Type I IFNs are produced early in viral infection and are one factor involved in the redistribution of lymphocytes from the peripheral blood into infected tissues [15,16]. …”
Section: Picornaviruses Suppress the Innate Immune Responsementioning
confidence: 99%
“…Mice infected with EV 71 failed to produce type I IFN in response to either poly(I:C) injection or CVB3 infection, both of which are strong inducers of type I IFN [14]. Type I IFNs are produced early in viral infection and are one factor involved in the redistribution of lymphocytes from the peripheral blood into infected tissues [15,16]. …”
Section: Picornaviruses Suppress the Innate Immune Responsementioning
confidence: 99%
“…Supporting the proposition that there are constraints on the number memory T cells in an animal, it has been shown that the size of the pool of LCMV-specific CD8 memory T cells declines when a mouse subsequently develops immunity to other viruses [111, 112]. Although others have reported long-term maintenance of cell numbers in the CD8 memory pool [15, 20, 31], these latter experiments are presumed to have been conducted in the absence of subsequent infections and hence the size of the memory T cell pool in the animals used may be small enough to avoid size constraints.…”
Section: Maintenance Of Memory Cellsmentioning
confidence: 99%
“…This slow division allows memory CD8ϩ T cells to maintain their numbers despite slow attrition due to cell death. The requirement for IL-15 may be one of the characteristics of CD8ϩ memory T cells, amongst others, which controls their numbers (10,11).…”
mentioning
confidence: 99%